Cancer theranostic platforms based on injectable polymer hydrogels. (26th February 2021) - Wang, Feifei; Chen, Jingsi; Liu, Jifang; Zeng, Hongbo
Abstract : The design of injectable polymer hydrogels for cancer theranostics is described, particularly focusing on the elements/components of theranostic hydrogels, and their cross–linking strategies, structures, and performance on drug delivery/tracking. Abstract : Theranostic platforms that combine therapy with diagnosis not only prevent the undesirable biological responses that may occur when these processes are conducted separately, but also allow individualized therapies for patients. Polymer hydrogels have been employed to provide well-controlled drug release and targeted therapy in theranostics, where injectable hydrogels enable non-invasive treatment and monitoring with a single injection, offering greater patient comfort and efficient therapy. Efforts have been focused on applying injectable polymer hydrogels in theranostic research and clinical use. This review highlights recent progress in the design of injectable polymer hydrogels for cancer theranostics, particularly focusing on the elements/components of theranostic hydrogels, and their cross-linking strategies, structures, and performance with regard to drug delivery/tracking. Therapeutic agents and tracking modalities that are essential components of the theranostic platforms are introduced, and the design strategies, properties and applications of the injectable hydrogels developed via two approaches, namely chemical bonds and physical interactions, are described. The theranostic functions of the platforms are highly dependent on the architecture and components employed for the construction of hydrogels. Challenges currently presented by theranostic platforms based on injectable hydrogels are identified, and prospects of acquiring more comfortable and personalized therapies are proposed.